Reading Opportunities in a Provincial Russian City during the First World War (Materials from the Volga Region) - E. Yu. Semenova (Научный диалог)
The article deals with the problem of resources for reading for the townspeople in the Volga city during the First World War. It is noted that the dealing with the problems, allows the researcher to identify the mechanisms that allowed society to adapt to the conditions of extreme reality. The provision of the Volga cities with libraries has been studied. The possibilities of reading in the provincial and district cities of the studied region are compared. The novelty of the research is seen in the fact that the development of a complex of public and private resources (libraries), available for leisure reading in the Volga city during the First World War, was revealed. The relevance of the study is due to the importance of analyzing the sociocultural practices of society as a compensatory mechanism, as well as a resource reflecting mass sentiment in extreme periods of state development. Comparison of provincial and county city libraries in terms of ownership, attendance, material security is carried out. The conclusion is made about the diversity of reading opportunities as a form of leisure for the Volga region residents during the First World War. The cities of the Volga region were identified, in which the resource of libraries was more diverse. It is shown that there were more libraries in the provincial towns than in the county ones; they had a different organizational basis and more complete funds.